Cytochrome c₄ - characterisation, location and effect of growth conditions - Brown, Kevin Robert (The University of Edinburgh, 1988)
The work described in this thesis deals with the properties, cellular location, effect of growth conditions and the redox properties of cytochrome c₄ from the bacterium Pseudomonas stutzeri 224.

Spectrally cytochrome c₄ is characterised by an α-peak maximum at 550nm and an α/ß ratio of 1.22-1.23. The mobility on SDS gels is dependent on the redox state of the haem iron and whether the haem is present or not.

The cellular location of cytochrome c⁴ was identified as being mainly membrane bound by purification of cytochrome c⁴ from both soluble and membrane fractions. Analysis of cytoplasmic, periplasmic and membrane fractions by haem stained gels confirmed that cytochrome c⁴ is mainly membrane bound and in addition demonstrated that soluble cytochrome c⁴ is located in the periplasm. Proteolysis experiments on right-side-out vesicles demonstrated that cytochrome c^ is associated with the periplasmic face of the membrane. Cytochromes c⁴ from soluble and membrane fractions of aerobic and nitrate grown cells were shown to be identical with respect to amino acid composition, spectra, ELISA and redox titration.

The levels of cytochrome c⁴ were shown to be virtually identical in both aerobic and nitrate grown Pseudomonas stutzeri, however, the distribution of cytochrome c⁴ between membrane and soluble fractions was affected by growth conditions with more membrane bound cytochrome c⁴ found in aerobically grown cells.

Redox titration of cytochrome c⁴ yielded sigmoidal Nernst plots which may be analysed in terms of two components of +300 and +190mV. Two models are proposed to explain the two redox potentials; (1) the haems are intrinsically different or (2) the haems have identical potentials in the oxidised form but addition of one electron makes the addition of a second much more difficult (negative cooperativity) . Proteolytic cleavage of the cytochrome with chymotrypsin yielded two fragments, one with a molecular weight of approx. 10000, a 695nm band and a midpoint potential of +110mV. The second fragment was damaged, as determined by the loss of the 695nm band, had a molecular weight of approx. 6000 and a midpoint potential of -190mV. Without two undamaged fragments it was not possible to distinguish between the two proposed models of reduction.

A partial characterisation of a c-type cytochrome of approx. 30000 molecular weight, which is greatly induced under nitrate growth, is also reported.